Hiroshima and Nagasaki - Claypool, Jane (Franklin Watts New York, 1984)
Discusses the planning for and the aftermath of the american use of the atomic bomb which destroyed two Japanese cities in August 1945.
Includes bibliography references and Index
Grade level : 7 - 9
Keywords: Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Juvenile literature; Nagasaki-shi (Japan) -- History -- Bombardment, 1945 -- Juvenile literature; Atomic bomb -- History -- Juvenile literature; Japan -- History -- Juvenile literature. -- 1912-1945